Findings of Abdominal Computed Tomography In COVID-19 Patients with Abnormal Abdominal Symptoms In Siriraj Hospital - Punyavik, Thanawat; Na Songkhla, Nithida; Muangsomboon, Kobkun (The ASEAN Journal of Radiology, 2024)
Background: The coronavirus (COVID-19) is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Chest imaging findings of COVID-19 disease have been widely published. Only a few studies of abdominal imaging findings have been documented. The majority of these studies demonstrate thrombotic events associated with COVID-19. Previous studies were mainly conducted in the USA, Europe and China which limited the applicability in Southeast Asia (SEA) including Thailand. Objective: To provide a summary of various abdominal imaging findings of COVID-19 patients admitted to xxx Hospital with findings associated with clinical outcomes. Materials and Methods: All CT abdominal imaging of adult patients who tested positive for COVID-19 performed from January 1st, 2020 to August 31st, 2022 were retrospectively reviewed. We collected clinical data, abdominal signs and symptoms, laboratory data and various CT findings, for example; bowel-wall thickening, bowel ischemia, fluid-filled colon and bleeding manifestations. The clinical outcomes were gathered as death confirmation, invasive mechanical ventilation, days of invasive mechanical ventilation and days of hospitalization. Results: A large number of patients who had stage 3-5 chronic kidney disease (CKD), abdominal distension, abnormal bowel findings and longer days of hospitalization were significantly observed in a group with worse clinical outcomes. Abnormal intestinal imaging findings were related to a higher risk of worse outcomes, invasive mechanical ventilation, death and days of hospitalization without statistical significance. Conclusion: Abdominal CT scans performed on COVID-19 patients frequently revealed abnormal bowel findings, which were strongly associated with poor clinical outcomes. Radiologists need to be concerned about abnormal bowel findings and point them out to clinicians and surgeons.